Neurological, cognitive and learning evaluation of students who were born preterm - André Luis Santos do Carmo; Fernanda Wagner Fredo; Isac Bruck; Joseli do Rocio Maito de Lima; Rebecca Nóbrega Ribas Gusso Harder Janke; Thais da Glória Messias Fogaça; Jacqueline Andrea Glaser; Tatiana Izabele Jaworski de Sá Riechi; Sergio Antonio Antoniuk (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To evaluate the cognitive and academic profile of preterm newborns at school age and to determine the factors related to prematurity and sociodemographic profile that influence these results. Methods: Patients aged 6-14 years old that were assisted in the preterm follow-up clinic were recruited. The cognitive, academic, and neurological capacities were accessed through a detailed evaluation with a child neurologist, a neuropsychologist and a psychopedagogue. Neonatal data were collected from patient records. Results: 97 children were included and 14 were excluded from the study, resulting in 83 children. Gestational age (GA) was 30±3 weeks and weight at birth was 1138g (605 to 4185g). Poor performance was shown in 38.4% for writing, 57.5% for reading and 42.5% for mathematics. The mean total intelligence quotient (IQ) was 96±14.9 points, and 10.9% were considered altered. Children with unstructured families presented 78.3% of failure in reading tests (p=0.029). The multivariate analysis showed association between GA at birth and classic mini-mental score (p=0.043), total IQ (p=0.047), perceptual organization IQ (p=0.035), and processing speed IQ (p=0.036). There was also association between weight at birth and the classic (p=0.004) and adapted (p=0.007) mini-mental scores; invasive mechanic ventilation duration and classic mini-mental (p=0.049); and lower maternal age and processing speed IQ (p=0.033). Conclusions: Preterm infants at school age had high frequency of failure in cognitive and academic evaluation tests. Learning difficulties are high among them. Multiple neonatal variables are related with altered cognitive and students development.